The Legal Position of Attorney’s Power Imposing Mortgage Rights in Providing Subsidized Home Ownership Credit Facilities - Heri Mulyono; Jawade Hafidz; Aryani Witasari (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2022)
This study aims to determine and analyze the legal position of the power of attorney imposing mortgage rights in the provision of subsidized housing credit facilities related to Article 15 paragraph (5) of Act No. 6 of 1994 concerning Mortgage Rights provides an exception for the period of time for the Power of Attorney to impose Mortgage Rights (SKMHT) granted to guarantee certain loans and the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of Act No. 22 of 2017 concerning Determination of the Deadline for the Use of Power of Attorney Imposing Mortgage to Guarantee the Repayment of Certain Loans. This study uses an empirical juridical approach that relies on primary field research data and the research specifications applied in this study are descriptive analytical with population and the sampling technique used is non-random sampling with purposive sampling. The results of this study indicate that the Power of Attorney to impose Mortgage has a function as a power of attorney addressed to the mortgage holder or other party to represent the mortgage giver himself present before the PPAT to carry out the encumbrance of the Mortgage, as well as a form of binding guarantees to creditors. In the event that the debtor is in arrears/defaults, the creditor can exercise his rights based on Article 1276 of the Civil Code, namely suing for matters to fulfill/implement the agreement.